2012
DOI: 10.1590/s0102-311x2012000400012
|View full text |Cite
|
Sign up to set email alerts
|

Incentivos para atraer y retener personal de salud de zonas rurales del Perú: un estudio cualitativo

Abstract: El objetivo fue identificar incentivos de atracción y retención en zonas rurales y distantes de Ayacucho, Perú. Fueron realizadas entrevistas en profundidad con 80 médicos, enfermeras, obstetras y técnicos (20 por grupo) de las zonas más pobres y con 11 funcionarios. No existen políticas sistemáticas de atracción y retención de personal de salud en Ayacucho. Los principales incentivos, en orden de importancia, fueron mejoras salariales, oportunidades de formación y capacitación, estabilidad laboral y nombramie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
30

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 15 publications
2
14
0
30
Order By: Relevance
“…As we showed in a related qualitative study, doctors, nurses, midwives and nurse technicians incentives all feel that the rural setting is clearly a disadvantageous place to remain for themselves and their families, and they therefore considered it as a place to stay only transiently, while waiting for better job opportunities [26].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…As we showed in a related qualitative study, doctors, nurses, midwives and nurse technicians incentives all feel that the rural setting is clearly a disadvantageous place to remain for themselves and their families, and they therefore considered it as a place to stay only transiently, while waiting for better job opportunities [26].…”
Section: Discussionmentioning
confidence: 80%
“…Unfortunately, this flexibility for hiring professionals for short-term periods is also related to job instability expressed by the fact that employees can be fired at any moment or may lose their job when their contract period ends [12], [16]. Therefore contratados may be willing to accept rural posts if they feel that in this way they will assure a position for a few years, as revealed by our related qualitative study [26]. Our current DCE also showed that lengthening the waiting time before getting a permanent post acted as a significant disincentive factor, although it was not particularly powerful, and therefore that decreasing this waiting time would act as a an incentive, a point we also discuss in the section on policy simulations.…”
Section: Discussionmentioning
confidence: 99%
“…These attributes were: type of health facility, monthly net income, time in post before getting a permanent job, points when applying for a residency in Community and Family Medicine after three years in post, provision of free housing, work schedule (excluding holidays), and number of allowance/free days for continuous medical education (Table 1). While our qualitative study performed before this DCE study found that nurses and midwives consistently expressed recognition for their jobs as a relevant incentive, this issue did not emerge strongly from the interviews and focus groups with doctors [24]. Therefore, we decided not to include this particular attribute in the final DCE design for doctors, whereas we included it in the final design for nurses and midwives.…”
Section: Methodsmentioning
confidence: 98%
“…The identification of the most relevant attributes and levels to include in the DCE relied on several methods: in-depth interviews and focus groups performed with health providers currently working in Ayacucho [24], review of the international literature on attraction and retention strategies in low and middle-income countries [1], and interviews with policy makers.…”
Section: Methodsmentioning
confidence: 99%
“…Incluso en Sudáfrica se refieren al servicio social de medicina como un periodo de "esclavitud" necesario para seguir con el desarrollo profesional (27) . Esto puede explicar la falta de atracción y la incapacidad en retener a los serumistas para trabajar en el futuro en las zonas vulnerables (28) ; con una "bola de nieve" de comentarios que influye en las decisiones de los futuros serumistas y profesionales que hayan culminado este programa (29) .…”
Section: Falta De Compromiso E Identificaciónunclassified